Wybrane charakterystyki oceny działania europejskich systemów ochrony zdrowia – perspektywa pacjenta - Aldona Frączkiewicz-Wronka; Konrad Laska (Problemy Zarządzania, 2013)
An aging population, progress in medical technology and rising public expectations of provided health services is just one of many challenges facing today’s health care systems. One of the key factors of research in the analyzed national health systems is the ability to effectively achieve its objectives. The Authors of this thesis, tempted to analyze the efficiency of system’s operations by discussing the assessments made by patients and consumers in European countries obtained using a similar methodology in the years 2007, 2009, 2012. The study was conducted by the research institute Health Consumer Powerhouse (HCP). Analysis covered the results of subjective evaluation of selected areas of health care system’s activity. Furthermore we characterized the expenditures and spending on health in these countries, which in EHCI were rewarded with the highest score. In conclusion, the authors have conducted the discussion which classic health care models seem to have a greater social acceptance and acquiescence for the action.